Exploring and Mitigating Cybersecurity Challenges in Electronic Health Records - Triplett, William J. (Cybersecurity and Innovative Technology Journal, 2024)
This study explores the complexities of cybersecurity challenges in electronic health record (EHR) systems and provides comprehensive solutions to enhance security. Furthermore, it analyzes existing research on EHR cybersecurity, considers relevant frameworks, and presents a well-designed research approach. Extensive research has examined the cybersecurity landscape of electronic health records (EHRs). Furthermore, it identifies the inherent flaws, challenges, and threats prevalent in existing systems and firmly emphasizes the need for robust security solutions to safeguard sensitive patient information. This study highlights the significance of addressing EHR cybersecurity concerns, enhancing existing knowledge on vulnerabilities, and providing a comprehensive understanding of this field. The study emphasizes the need for proactive and multifaceted security measures that can adapt to the ever-evolving landscape of cyber threats. Future research must continue to explore innovative tools and methodologies to safeguard EHRs against the increasing complexity and sophistication of cyber threats.